Design of stand-alone photovoltaic system using evolutionary programming / Nurul Suzalia Asmani - Asmani, Nurul Suzalia (2013)
This paper presents an intelligent sizing technique for sizing stand-alone photovoltaic (SAPV) system in rural area at Selangor using Evolutionary Programming (EP). The chosen rural area was Kampung Orang Asli Paya Lebar, Hulu Langat Selangor. Meteorological data and electrical load data of household of considered site location are taken into account during sizing steps. The main concern for designing the SAPV system is power reliability of the system designed under whether varying weather condition. The decision variables of this optimization process are number of PV modules and batteries used. However, the objective function of this process is to maximize the technical performance of the system. In order to maximize the technical performance of this system, the indicator used is Loss of Power Supply Probability (LPSP). The LPSP results are compared with different type of EP named Classical EP (CEP) and Fast EP (FEP).